Morphological and genetic divergence between Mediterranean and Caribbean populations of Madracis pharensis (Heller 1868) (Scleractinia, Pocilloporidae): too much for one species? - Benzoni, Francesca; Arrigoni, Roberto; Berumen, Michael L .; Taviani, Marco; Bongaerts, Pim; Frade, Pedro R. (Zootaxa, 2018)
The colonial stony coral genus Madracis is cosmopolitan, lives in shallow and deep water habitats, and includes zooxanthellate, azooxanthellate and facultative symbiotic species. One of its species, Madracis pharensis, has been recorded from the Mediterranean and East Atlantic, where it forms small knobby and facultative zooxanthellate colonies (also named M. pharensis f. pharensis), and from the tropical Caribbean, where it also occurs in a massive and zooxanthellate form (named M. pharensis f. luciphila by some). These two forms have been previously found to host different Symbiodinium species. In this study, species boundaries and phylogenetic relationships between these two Madracis pharensis forms (from the Mediterranean Sea and the Caribbean), M. senaria, and the Indo-west Pacific M. kirbyi were analyzed through an integrated systematics approach, including corallite dimensions, micromorphology and two molecular markers (ITS and ATP8). Significant genetic and morphological differences were found between all the examined Madracis species, and between M. pharensis from the Mediterranean Sea and M. pharensis f. luciphila from the Caribbean in particular. Based on these results, the latter does not represent a zooxanthellate ecomorph of the former but a different species. Its identity remains to be ascertained and its relationship with the Caribbean M. decactis, with which it bears morphologic resemblance, must be investigated in further studies. Overall, the presence of cryptic Madracis species in the Easter and Central Atlantic Ocean remains to be evaluated.